2015
DOI: 10.1007/s10948-015-3078-6
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Fluctuations and Excess Conductivity Analysis of Te-Substituted TlSr2(Ca1−x Te x )Cu2O7−δ

Abstract: Samples with nominal starting compositions TlSr 2 (Ca 1−x Te x )Cu 2 O 7−δ (x = 0.05-0.30) were prepared by the solid-state reaction method and studied by powder X-ray diffraction and electrical resistance measurements. The purpose of this work was to determine the valence state of Te in the TlSr 2 CaCu 2 O 7−δ (Tl-1212) phase. It is also to determine the dimension of fluctuation-induced conductivity λ, and the superconducting fluctuations and excess conductivity using the Aslamazov-Larkin (AL) theory. The Law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The c lattice parameter increased as Te was substituted, and this may be due to the ionic radius of Te 4+ = 0.97 Å being substituted for smaller Tl 3+ = 0.885 Å. Hence, it is suggested that the effective ionic radius for this work is Te 4+ = 0.97 Å in comparison to Te 6+ = 0.56 Å [25] as a result of the increment in the lattice parameters. The decreasing trend of the c lattice parameter with the substitution of Cr, Bi, Pb, and Se as in Table 1 is possibly due to their smaller ionic radii being substituted at the Tl site.…”
Section: Xrd Patternsmentioning
confidence: 84%
“…The c lattice parameter increased as Te was substituted, and this may be due to the ionic radius of Te 4+ = 0.97 Å being substituted for smaller Tl 3+ = 0.885 Å. Hence, it is suggested that the effective ionic radius for this work is Te 4+ = 0.97 Å in comparison to Te 6+ = 0.56 Å [25] as a result of the increment in the lattice parameters. The decreasing trend of the c lattice parameter with the substitution of Cr, Bi, Pb, and Se as in Table 1 is possibly due to their smaller ionic radii being substituted at the Tl site.…”
Section: Xrd Patternsmentioning
confidence: 84%
“…A minor Tc substitution in the Tl-2223 phase at Ca site boosted Tc to 120 K and substantially encouraged the formation of the Tl-2223 phase in bulk samples [14]. The transition temperature, Tc, of TlSr2Ca1-xTexCu2O7 improved as the Te content rose [15]. Tc was found to be around 92 to 97 K when Te was substituted in (Tl0.5Pb0.5)Sr2CaCu2O7 [16].…”
Section: Introductionmentioning
confidence: 97%
“…The formation of conducting pairs just above Tc has been attributed to superconducting order parameter fluctuations, which plays an important role in specifying the superconducting properties [11][12][13][14]. For better understanding the intrinsic properties of the superconductors such as coherence lengths, the effective inter-layering spacing and the interlayer coupling strength between the two CuO2 layers, variations of excess conductivity versus reduced temperature (t = (T -Tc)/Tc) were analyzed by using the Aslamazov-Larkin (AL) and Lawrence -Doniach (LD) models [11,13].…”
Section: Introductionmentioning
confidence: 99%